How skilled immigration may improve economic equality - Martin Kahanec; Klaus F. Zimmermann (IZA Journal of Migration, 2014)
Mobile workers involve flows of labor and human capital and contribute to a more efficient allocation of resources. However, migration also changes relative wages, alters the distribution of skills and affects equality in the receiving society. The paper suggests that skilled immigration promotes economic equality in advanced economies under standard conditions. This is discussed and theoretically derived in a core model, and empirically supported using unique data from the WIID database and OECD.
Keywords: D33; E25; F22; J15; J61; O15; 330; Inequality; Income distribution; Human capital; Skill allocation; Migration; Ethnicity; Minority; Gini coefficient